2014
DOI: 10.1111/apha.12287
|View full text |Cite
|
Sign up to set email alerts
|

Modular organization of cardiac energy metabolism: energy conversion, transfer and feedback regulation

Abstract: To meet high cellular demands, the energy metabolism of cardiac muscles is organized by precise and coordinated functioning of intracellular energetic units (ICEUs). ICEUs represent structural and functional modules integrating multiple fluxes at sites of ATP generation in mitochondria and ATP utilization by myofibrillar, sarcoplasmic reticulum and sarcolemma ion-pump ATPases. The role of ICEUs is to enhance the efficiency of vectorial intracellular energy transfer and fine tuning of oxidative ATP synthesis ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 171 publications
(250 reference statements)
1
46
2
Order By: Relevance
“…Actually, a previous study showed that VDAC is involved in cardiac energy metabolism [60]. Although we demonstrated that RNF207 promotes the polyubiquitination of VDAC1, RNF207 does not affect the stability of VDAC1.…”
Section: Discussioncontrasting
confidence: 60%
“…Actually, a previous study showed that VDAC is involved in cardiac energy metabolism [60]. Although we demonstrated that RNF207 promotes the polyubiquitination of VDAC1, RNF207 does not affect the stability of VDAC1.…”
Section: Discussioncontrasting
confidence: 60%
“…A bulk of energy production is directed to contractile function of the heart. As NADH and FADH2 are generated from both fatty acid oxidation as well as the TCA cycle (and lesser extent from glycolysis), protons are transported through the electrochemical gradient between the mitochondrial matrix and the intermembrane space via the F0F1 ATPase and storage of the resultant chemical energy as ATP bound to membrane-associated cytoskeletal elements (79). …”
Section: Cardiac Energetics Substrate Metabolism and Pathophysiologymentioning
confidence: 99%
“…This compartmentalization of myocardial energetic units helps optimize the efficiency of nutrient and oxygen delivery as well as rapidly regenerating ATP from ADP produced by the contractile elements rather than being dependent on diffusion gradients and a diffuse distribution throughout the cell. ATP and ADP, themselves, appear to be attached to cytoskeletal structures rather than free in the cytosol (79). This is important with regards to being able to control the availability of high-energy phosphates to the cardiac myofilaments.…”
Section: Cardiac Energetics Substrate Metabolism and Pathophysiologymentioning
confidence: 99%
“…Thus, the cytosolic ADP, Pi and Cr signals are transformed into a PCr energy flux maintained by the MtCK reaction. As a result, the reactions catalyzed by different isoforms of compartmentalized CK, organized in intracellular energetic units (ICEUs; Saks et al 2012;Guzun et al 2015), tend to maintain the intracellular metabolic stability Aliev et al 1998;Vendelin et al 2000).…”
Section: Proteolipid Complexes Involving Mitochondrial Creatine Kinasmentioning
confidence: 99%